Cooperation between Police and Private Security in Emergency Situations in the Republic of Serbia – Current State and Possibilities - Lončar, Zoran; Radivojević, Nenad; Radošević, Ratko; Mirković, Vladan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Emergency situations require special and additional activities from the state authorities, as well as from different private bodies and subjects. Among state authorities important role is given to the Ministry of internal affairs; among private bodies and subjects, important role could be given to the private security. Starting from that position, the authors are trying to find the way of using private security bodies in emergency situations, in cooperation with the police. Aim of the authors is to critically analyze our legislation and to recommend the means of this cooperation.